Massive Mature Mediastinal Teratoma With Malignant Transformation: An Unusual Case Report - Karla Kalua; Widiastuti Soewondo (Indonesian Journal of Medicine, 2024)
Background: Teratoma is a type of germ cell tumor that is rarely found in the anterior mediastinum. Meanwhile, mature mediastinal teratoma with malignant transformation is rare and develops rapidly, with a poor prognosis. This article aims to report one of the uncommon cases of mature teratoma and discuss its imaging features thereby adding insight in providing an accurate diagnosis of this condition. Case Report: This study presents a case of a 26-year-old male patient who has complained of shortness of breath for 3 months and worsening in the last 3 days. The patient passed through a chest radiographic examination and was diagnosed with a mediastinal tumor. The contrast-enhanced chest computed tomography showed a huge mediastinal mass occupying the right and left hemithorax, measuring 16.9 cm x 20.5 cm x 20.9 cm and pressing against the chest wall, esophagus, trachea, great vessels, and the vital organs, lungs as well as heart, causing several complications in patients. Conclusion: Knowledge of the teratoma radiological appearance and the characteristics of the various subtypes is very important in the diagnosis of mediastinal teratoma diagnosis for immediate and appropriate treatment.